PENGARUH PENAMBAHAN KARBON AKTIF DAN PEMAKAIAN SCRUBBER CO2 TERHADAP KUALITAS DAN KUANTITAS BIOGAS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
I. Economic and Social Commission for Asia and the Pacific. Updated Guidebook on Biogas Development Series, No. 27, 85 â 89. 2. Chynoweth, D.P., dkk. 1982. Kinetics and Advanced Digester Design for Anaerobic Digestion of Water Hyacinth and Primary Sludge. Biotechnology and Bioengineering